Law and Gospel, and Youth and Family Ministry - Wiersma, Hans (Dialog, 2008)
If “faith comes through hearing” the word of God comprised in law and gospel, how do the imperatives that characterize ‘Youth and Family Ministry’ make such hearing possible? Here, literature delineating ‘Youth and Family Ministry’ is analyzed in light of its biblical foundations. The primary lens implemented in this analysis is the law/gospel hermeneutic advocated by Martin Luther and other reformers.